2010
DOI: 10.1088/0031-8949/81/03/035302
|View full text |Cite
|
Sign up to set email alerts
|

Coherent states for PT-/non-PT-symmetric and non-Hermitian Morse potentials via the path integral method

Abstract: We discuss the coherent states for PT-/non-PT-Symmetric and non-Hermitian generalized Morse Potential obtained by using path integral formalism over the holomorphic coordinates. We transform the action of generalized Morse potential into two harmonic oscillators with a new parametric time to establish the parametric time coherent states. We calculate the energy eigenvalues and the corresponding wave functions in parabolic coordinates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In recent years, there has been an increased interest in finding exact solutions to relativistic spinless KG particles with various vector and scalar potentials [3 -8]. The most commonly used techniques to explore these wave equations are the NikiforovUvarov (NU) method [9 -12], the super-symmetric quantum mechanics method [13,14], the point canonical transformation [15,16], the asymptotic iteration method [17,18], the proper quantization rule [19,20], the shifted large 1/N expansion (SE) technique [21], and the ansatz approach [22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increased interest in finding exact solutions to relativistic spinless KG particles with various vector and scalar potentials [3 -8]. The most commonly used techniques to explore these wave equations are the NikiforovUvarov (NU) method [9 -12], the super-symmetric quantum mechanics method [13,14], the point canonical transformation [15,16], the asymptotic iteration method [17,18], the proper quantization rule [19,20], the shifted large 1/N expansion (SE) technique [21], and the ansatz approach [22].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] This equation is solved by means of different methods for exactly solvable potentials. [9][10][11][12][13][14][15][16][17][18][19][20] Aydoǧdu and Sever investigated the exact solution of the Dirac equation for Mie-type potentials by asymptotic iteration method 21 and for pseudoharmonic potential by using the Nikiforov-Uvarov method. 22 Jia et al found exact solution of Dirac equation for the Eckart potential with spin and pseudospin symmetry by using the approach supersymmetric quantum mechanics and the function analysis method.…”
Section: Introductionmentioning
confidence: 99%
“…In the non-relativistic limit, the Schrödinger solution can be obtained from the S(r) = V (r) case by means of (13). Applying the transformations E nl + M ≈ 2µ/h 2 , E nl − M ≈ E nl , one obtains the energy formula…”
Section: The Non-relativistic Limitmentioning
confidence: 99%
“…In recent years, there has been an increased interest in finding exact solutions to relativistic spinless KG particles with various vector and scalar potentials [3 -8]. The most commonly used techniques to explore these wave equations are the Nikiforov-Uvarov (NU) method [9,10], the supersymmetric quantum mechanics method [11,12], the point canonical transformation [13], the iteration method [14 -16], the exact quantization rule [17], the shifted 1/N expansion (SE) technique [18], and the ansatz approach [19].…”
Section: Introductionmentioning
confidence: 99%